Children and Adults Use Physical Size and Numerical Alliances in Third-Party Judgments of Dominance - Lourenco, Stella F.; Bonny, Justin W.; Schwartz, Bari L. (Frontiers in Psychology, 2016)
Humans and other social animals interact regularly with conspecifics as part of affiliative groups. Many of these interactions are cooperative, but many others involve competition for resources. Competitive exchanges are often resolved on the basis of dominance relationships, with higher-ranking individuals receiving priority access to desired goods. Although no single cue can establish permanent dominance relationships, there are some cues that predict dominance fairly reliably across context. In the present study, we focused on two such cues relevant to competing groups: (i) the physical sizes of individual members, and (ii) their relative number. Using a social competition task, we examined whether, and how, preschool-aged children and adults used differences in physical size and numerical alliances to judge which of two groups should prevail in a competitive exchange for a desired object. These judgments were made when either physical size or number differed between groups (Experiment 1), and when both were available but pitted against each other (Experiments 1 and 2). Our findings revealed that by 3 years of age, humans use multiple perceptible cues in third-party judgments of dominance. Our findings also revealed that 3-year-olds, like adults, weighted these cues flexibly according to the additional factor of overall group size, with the physical sizes of individuals determining dominance in smaller groups (e.g., 2 vs. 4 characters) and the relative number of individuals determining dominance in larger groups (e.g., 15 vs. 30 characters). Taken together, our findings suggest that a basic formula for determining dominance in competitive exchanges, which weights physical size of individuals and numerical alliances as a function of overall group size, is available to young children and appears fairly stable through to adulthood.